Optimization of Control Strategies for the Radiant Floor Cooling System Combined with Displacement Ventilation: A Case study of an Office Building in Jinan, China - Jiying Liu; Jing Ren; Linfang Zhang; Xiaona Xie; Moon Keun Kim; Linhua Zhang (International Journal of Architectural Engineering Technology, 2019)
The radiant floor cooling system, as a thermally activated building system, has attracted significant attention as it can save energy consumption and shift the building load. However, due to its characteristic that building thermal mass has a significant influence on the system performance and indoor environment, the control strategies should be seriously accounted for. Moreover, its performance is highly related to the shift condition of cooling load during the daytime and different weather conditions, therefore, realistic operation will cause the increments of peak load if the control strategy is neglected. This study presented two common strategies including intermittent operation and weatherforecast-based control strategies. The radiant floor cooling system combined with displacement ventilation system in a typical office building located in Jinan was established using the TRNSYS program. The results showed that the energy consumption decreased by 3.3% to 7.5% when the different intermittent operation strategies were applied. The weatherforecast- based control strategy can improve indoor thermal environment by increasing/deceasing the water supply flow rate by up to 25% in advance. This study concluded that the application of intermittent operation and weather-forecast based control strategies can regulate the operation of radiant floor system and reduce the building energy use.